2013
DOI: 10.1002/chem.201300243
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electron Behavior in Nano‐TiO2 Photocatalysis by Using In Situ Open‐Circuit Voltage and Photoconductivity Measurements

Abstract: The in situ open-circuit voltages (Voc ) and the in situ photoconductivities have been measured to study electron behavior in photocatalysis and its effect on the photocatalytic oxidation of methanol. It was observed that electron injection to the conduction band (CB) of TiO2 under light illumination during photocatalysis includes two sources: from the valence band (VB) of TiO2 and from the methanol molecule. The electron injection from methanol to TiO2 is slower than that directly from the VB, which indicates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Photoexcitation and electrochemical reduction can inject non-thermal excess electrons in TiO 2 [170,171]. Excess holes are mainly created by photo-excitation for n-type semi-conductors, such as TiO 2 , ZnO, and other oxide materials, which are seldom studied as compared to the electrons [172,173]. Excess electrons and holes can be delocalized at the CB and the VB extended states, self-localized at regular lattice sites, or localized around defect sites.…”
Section: Physiochemical Nature Of Gap States: Charge Carrier Localizamentioning
confidence: 99%
“…Photoexcitation and electrochemical reduction can inject non-thermal excess electrons in TiO 2 [170,171]. Excess holes are mainly created by photo-excitation for n-type semi-conductors, such as TiO 2 , ZnO, and other oxide materials, which are seldom studied as compared to the electrons [172,173]. Excess electrons and holes can be delocalized at the CB and the VB extended states, self-localized at regular lattice sites, or localized around defect sites.…”
Section: Physiochemical Nature Of Gap States: Charge Carrier Localizamentioning
confidence: 99%
“…Recently, we studied the thermodynamic driving force of photocatalytic oxidation of methanol by nano-TiO 2 under UV light irradiation. 52 As shown in Fig. 3, the nano-TiO 2 changes from thermal equilibrium state to non-equilibrium state due to the excess electron production in the CB, as indicated by the change of Fermi level of electrons.…”
mentioning
confidence: 94%
“…As an example, the electron injection from methanol to TiO 2 can increase the electron Fermi level from 0.52 to 0.65 eV. 52 The 0.13 eV difference of Fermi level forms the thermodynamic driving force of photocatalytic oxidation of methanol.…”
mentioning
confidence: 99%
“…They suggested that the transient photoconductivity of a nanocrystalline TiO2 film in vacuum was governed by the thermal re-lease of electrons from the trap states in the bandgap. Liu et al [12][13][14] successfully employed in situ temperature-dependent photoconductivity to understand the photocatalytic degradation of gaseous formic acid in air. They revealed that the electron transfer was determined by the interface transfer of electrons to O2 rather than by the transport.…”
Section: Introductionmentioning
confidence: 99%